Indonesian Tourist Satisfaction towards GWK Cultural Park Using Importance-Performance Analysis (IPA) as a Tool to Determine Improvement Priorities - Tirtawati, NI Made; Negarayana, Ida Bagus Putra; Julianti, Ni Kadek Intan (Jurnal Penelitian Pariwisata, 2023)
This research aims to identify the level of satisfaction of Indonesian tourists, the tourism product attributes that need improvement, and the loyalty of Indonesian tourists towards the tourism products at GWK Cultural Park. This research employs a quantitative method with 100 samples collected through accidental sampling. Primary data collection is conducted through questionnaires, field observations, and documentation. The analysis methods used in this research are the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA). The research findings indicate that the satisfaction index of Indonesian tourists stands at 84%, indicating that Indonesian tourists are delighted with the tourism products at GWK Cultural Park. Based on the Importance-Performance Analysis (IPA) results, the top priorities that the management should implement to enhance the satisfaction of Indonesian tourists are providing tourist attractions that match the price paid, having staff who quickly process entrance tickets, and ensuring that the tourist area is free from unpleasant odors. The level of loyalty among Indonesian tourists in the attitudinal loyalty category is 18%, the behavioral loyalty category is 45%, and the composite loyalty category is 37%. This research demonstrates that tourist attractions that align with the price paid, responsive staff, and an odor-free environment are crucial in enhancing the satisfaction of Indonesian tourists, who have an 82% chance of becoming repeat guests at GWK Cultural Park. Keywords: tourist satisfaction, tourist loyalty, Indonesian tourists, tourism products, Garuda Wisnu Kencana cultural park